PENGARUH MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KEMANDIRIAN BELAJAR DAN KEMAMPUAN MENULIS TEKS PROSEDUR KOMPLEKS SISWA KELAS XI SMA NEGERI 3 BANGKALAN - Veranita, Yuliawati; Sucipto, Sucipto; Utami, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aims of the research are: 1) to test the influence of the concept sentence learning model on the learning independence of class To test the effect of the concept sentence learning model on learning independence and the ability to write complex procedural texts for class XI students at SMA Negeri 3 Bangkalan. This research is a quantitative experimental study using the independent sample t test analysis technique. The sample in this study was 30 students of class XI IPA 1 as the experimental group and 30 students of class Bangkalan, 2) There is an influence of the concept sentence learning model on the ability to write complex procedural texts for Class XI students of SMA Negeri 3 Bangkalan, and 3) there is an influence of the concept sentence learning model on learning independence and Ability to Write Complex Procedure Texts for Class XI Students of SMA Negeri 3 Bangkalan.